Insight from health professionals on physical activity promotion within routine diabetes care. (April 2014) - Matthews, Lynsay; Kirk, Alison; Mutrie, Nanette
Abstract The aim of this qualitative study was to explore the views of health professionals on the current and future provision of physical activity promotion within routine diabetes care. Responses were collected from participants (n=23) in two phases. An online survey (Phase 1, n=16) and semi‐structured interviews (Phase 2, n=7) were used to explore the experiences of health professionals on the provision of physical activity promotion. Qualitative responses were analysed using Interpretative phenomenological analysis and categorised into themes and sub‐themes. Three main themes were identified: (1) current physical activity promotion practices; (2) delivery of physical activity promotion by health professionals; and (3) future physical activity promotion. Findings demonstrated that a lack of structure for physical activity promotion and ineffective behaviour change training made physical activity promotion within routine diabetes care challenging. Health professionals struggled to prioritise physical activity within routine consultations. They were clinically driven to provide physical activity advice to patients; however, they lacked the skills to elicit significant behaviour change. Five recommendations were presented to improve physical activity promotion within diabetes care: (1) having a key member of staff responsible for physical activity promotion; (2) access to a referral route for physical activity support; (3) inclusion of diabetes‐specific information in behaviour change training; (4) linking the delivery of physical activity promotion with clinical outcomes; and (5) using 'champions' to raise the profile of physical activity within the health service. Incorporation of these recommendations by health professionals and health boards may significantly improve the provision of physical activity promotion within routine diabetes care. Copyright © 2014 John Wiley & Sons.